2006
DOI: 10.1586/14787210.4.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Prulifloxacin: a new antibacterial fluoroquinolone

Abstract: In the last few years, the antimicrobial activity, efficacy and relative safety of fluoroquinolones have made them attractive for the treatment of community-acquired and nosocomial infections. Prulifloxacin is a new fluoroquinolone antibacterial agent with a broad spectrum of activity against Gram-positive and -negative bacteria. Prulifloxacin is available for oral use, and after absorption is metabolized in to the active form, ulifloxacin. It exhibits good penetration in target tissues and a long elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Prulifloxacin, the prodrug of ulifloxacin, is a new oral fluoroquinolone antibacterial agent, with a broad-spectrum of antibacterial activity and a good clinical and bacteriological efficacy [10][11][12][13][14]. Randomized comparative studies in patients with uncomplicated or complicated lower UTIs showed high eradication and clinical success rates, greater or at least as high as those of ciprofloxacin, amoxicillin/ clavulanic acid, or pefloxacin [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Prulifloxacin, the prodrug of ulifloxacin, is a new oral fluoroquinolone antibacterial agent, with a broad-spectrum of antibacterial activity and a good clinical and bacteriological efficacy [10][11][12][13][14]. Randomized comparative studies in patients with uncomplicated or complicated lower UTIs showed high eradication and clinical success rates, greater or at least as high as those of ciprofloxacin, amoxicillin/ clavulanic acid, or pefloxacin [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Prulifloxacin is converted to its active form, ulifloxacin, following oral administration and intestinal absorption (2,11,15,16). This fluoroquinolone is administered orally as a 600-mg tablet once daily and has been shown to maintain high concentrations within the gastrointestinal tract (12,16).…”
mentioning
confidence: 99%
“…displaying resistance to nalidixic acid and susceptibility to ciprofloxacin were a worrisome finding, being indicative of first-step mutations in the quinolone resistance-determining region. However, prulifloxacin levels in the bowel remain higher than those of other peer drugs due to 50% absorption (11,12,16).…”
mentioning
confidence: 99%
“…Its Gram-positive spectrum includes streptococci, S. pneumoniae and MSSA, but not MRSA. The compound targets urinary tract and respiratory tract infections [111].…”
Section: Prulifloxacin Prulifloxacin (Optimer) Is a New Quinolone Thamentioning
confidence: 99%